Design of a Multi Mode Interferometer using LC:PDMS technology. (3rd May 2019) - Civita, L.; Quaranta, S.; Asquini, R.; d'Alessandro, A.
Abstract: Multimode interference (MMI) couplers have received more attention in recent years due to their significant role played in telecommunications. Their unique features are compactness, relaxed design constrains, large optical bandwidth. In this paper a theoretical analysis and design of a MMI acting as multi/demultiplexer based on liquid crystals (LC) embedded in polydimethylsiloxane (PDMS) channels named LC:PDMS waveguides is presented. Such a device is capable of operating at two different wavelengths, typically used in erbium-doped fiber optical amplifiers, 980 and 1550 nm with an extinction ratio higher than 11 dB. The LC:PDMS MMI operation is tuned by applying an electric field by using coplanar electrodes whose fabrication process is described.